Investigation of the oviposition and predation impact on Dendroctonus micans (Kug.) of wild and laboratory-produced Rhizophagus grandis Gyll. on oriental spruce in Türkiye - Alkan Akıncı, Hazan; Grégoire, Jean-Claude (International journal of tropical insect science, 2025)
Dendroctonus micans (Kugelann) (Coleoptera: Curculionidae) is a primary pest of spruce in Eurasia. It has killed millions of spruce trees especially at the edges of its expanding range. In Türkiye and Caucasus, the beetle’s predominant host is oriental spruce, Picea orientalis (L.) Link. Sanitary thinning and clearfelling and, when allowed, chemical measures were not sufficient to control D. micans . Rhizophagus grandis Gyll. (Coleoptera: Monotomidae), a specific predator of D. micans , has been mass reared and released at infested stands, and is now considered as the major component in outbreak control. So, managing R. grandis from the rearing stage to the release in the infested stands is an important process. The oviposition and impact on D. micans on oriental spruce of wild and laboratory-produced R. grandis were compared under laboratory conditions in polystyrene boxes containing fresh P. orientalis bark and re-hydrated bark powder. Two series of experimental boxes were prepared. Each box contained twenty L2-L3 D. micans larvae as well as a pair of wild (series 1), or laboratory-produced (series 2), R. grandis adults. A pair of wild R. grandis yielded significantly more larvae than laboratory-produced predators. Predation was proportional to the number of predator larvae in the two groups after the first two weeks, but prey supply of the wild predators was nearly exhausted after two weeks. On the third week, predation was still proportional to the number of offspring of the laboratory-produced parents, but this was not the case with the wild predator larvae, as their prey supply had already been almost completely exhausted during the previous period. The offspring of the wild predators decreased after the second week, probably corresponding to cannibalism due to shortage of prey, whilst those of the laboratory-produced predators continued to increase in numbers between the second and the third week.